3D-Printed Absorbers for Solar-Driven Interfacial Water Evaporation: A Mini-Review - Tijing, Leonard; Dizon, John Ryan; Cruz Jr., Gil (Universitas PGRI Semarang, 2021)
Solar-driven interfacial water evaporation (SWE) is considered as a promising sustainable solution for clean water production especially for remote and off-grid communities. Various approaches have been developed in the last decade to improve the evaporation and thermal efficiency of the system, and to make it more robust for long-term operation. In recent years, 3D printing has emerged as an attractive method to fabricate simple and complex absorber geometries for SWE. In this mini-review, we present the new developments of 3D-printed solar absorbers including the various designs, fabrication strategies, challenges and opportunities. This study hopes to provide more insights into the use of additive manufacturing for improving the absorber design and performance of SWE.